Multi-receiver authentication code for network coding - Oggier, Frederique (2009)
Systems exploiting network coding suffer greatly from pollution attacks which consist of injecting malicious packets in the network. The pollution attacks are amplified by the network coding process resulting in a greater damage than under traditional routing. In this paper, we address this issue